edukasi perlindungan biota akuatik di kawasan Gampong Alue Naga sebaga peningkat ekonomi masayarakat - Ibrahim, Ibrahim; Rafsanjani, Aiza; Jalaluddin, Jalaluddin; Nurul Akmal; Mohd Isha Awang (Universitas Islam Negeri Ar-Raniry, 2026)
The estuarine area of Gampong Alue Naga supports high aquatic biodiversity and serves as a primary livelihood source for the local coastal community. However, ecological pressures such as overfishing, mangrove habitat degradation, and water pollution have led to a decline in economically valuable species. The research method used was quantitative descriptive with a participatory approach (participatory action research). Data collection used purposive sampling. The research instruments used were observation guidelines, interviews, and field documentation. Data analysis used quantitative descriptive. The findings indicate the presence of more than 40 aquatic species, including molluscs, crustaceans, and fish, such as Anadara granosa, Scylla serrata, and Penaeus monodon, which hold significant economic value. However, a reduction in size and population was observed in several key species. Community-oriented conservation education integrating local ecological knowledge, sustainable harvesting practices, and value-added seafood processing is recommended to maintain ecological balance and strengthen local economic resilience. Therefore, participatory environmental education plays a strategic role in achieving sustainable ecosystem management and improving coastal community welfare. Keywords: Aquatic biodiversity; Coastal economy; Conservation; Estuary; Environmental education